The effectiveness of the five-step strategy (SQ3R) in developing reading comprehension skills for sixth grade primary school students - Al-Ghamdi, Khaled Mohammed (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to measure the effectiveness of the five-step strategy (SQ3R) in developing reading comprehension skills, and knowing the necessary reading comprehension skills for sixth graders. To achieve the goal of the study, the researchers used the semi-experimental approach, which is based on the experimental and control groups, and use the pre-measurement to control the experimental procedures, then the post-measurement to study the differences and their significance between the experimental group. The researchers designed a number of research materials and tools: Reading comprehension skills list, Reading comprehension skills test, Learner’s Guide to Implementing the Five-Step Strategy (SQ3R). The study was applied to a random sample consisting of 60 students from the sixth regular primary school students in the academic year 1441 H - 2019 at Prince Saud bin Abdul Mohsen Elementary School in Jeddah, they were divided into two equal groups (30) students, one is experimental and the other is a control. The study reached the following results: There were statistically significant differences at the level of a <0.05 between the mean scores of the students of the experimental group and the control in the post test of reading comprehension skills related to the literal, explanatory and applied levels after controlling for pre-performance. And there is a practical indication that confirms the effectiveness of using the five-step strategy (SQ3R) in developing reading comprehension skills, meaning that the effect that occurred in the students’ level is due to the use of the strategy. The study recommended that those in charge of planning and developing Arabic language curricula be invited to employ modern strategies in reading education, and prepare procedural guides to help teachers use modern strategies, including the Five Steps Strategy (SQ3R).